Nitrogen Deposition in Different Mediterranean Forest Types along the Eastern Adriatic Coast - Lovreškov, Lucija; Limić, Ivan; Butorac, Lukrecija; Jakovljević, Tamara (2021)
Mediterranean forests along the eastern Adriatic coast have an important ecological role. However, few studies have been conducted on nitrogen deposition so far. To improve this knowledge, the main aims of our study were: (i) to estimate nitrogen inputs and determine differences among the four Mediterranean forests, (ii) to determine the seasonal behaviour of N deposition compounds, and (iii) to discuss the results in relation to forest type and precipitation. Measurements were carried out over a two-year period on four plots in two regions: holm oak and pubescent oak in Istria, Aleppo pine and black pine in Dalmatia. Bulk open field and throughfall deposition were sampled with continuously exposed collectors. Measurements, analyses and data validation of precipitation and N compounds were carried out. The results showed that the highest average monthly precipitation was recorded in the black pine plot and the lowest in the Aleppo pine plot. Nitrate and ammonia in conifer plots in throughfall samples were lower than in bulk open field samples, indicating possible retention by the tree canopy. The results revealed a higher amount of N deposition collected in broadleaved forests than in conifer forests indicating the washing out of N compounds previously deposited and accumulated in forest canopy. The chemistry of N deposition was strongly influenced by local and anthropogenic sources as well as neighbouring countries. Our results may fill the knowledge gap in understanding the influence of precipitation and seasonality of N compounds in different Mediterranean forest types along the eastern Adriatic coast.
Bibliografija
Summary.